Introdcution to Proteins: Structure, Function, and Motion - Amit Kessel, Nir Ben-Tal (Boca Raton CRC Press, 2018)
School of Biosciences
MIR No.: 201
Order Date: 2024-08-19
Order No: CU/OPEX/LIBRARY/26/2024-25
Received Date: 2024-11-13
Keywords: Biology, Biochemistry, Proteins